54 Palliative care should be offered to more liver disease patients earlier. (30th January 2023) - Walton, Sharon; Rolfe, Liz; Verne, Julia
Abstract : Introduction: Alcoholic related liver disease (ArLD) deaths and hospital admissions continue to rise. Hospital admissions are associated with high risk of mortality in the admission and within the following two months, yet few liver disease patients have palliative care input. Aims: To describe, using national mortality and hospital admissions data the special features of people dying of liver disease heightening their need for early palliative care input. Methods: People who died from liver diseases as underlying causes were identified from a linked Office for National Statistics (ONS) national mortality and hospital episode statistics (ONS-HES) dataset. Descriptive statistics of patient sociodemographics, place of death and aspects of their emergency admissions in the last year of life (EALoL) were generated. Results: 1 in 6.7 people who died from ArLD in 2020 were aged <44 years, 1 in 2.3 < 55. 61% of deaths were in males. There was 4.7 fold higher age standardised <75 mortality from ArLD in the most deprived decile compared to the least, 4.6 and 9.3 fold differences for Hepatitis B and C related deaths. Substance misuse was associated with these deprivation differences. 71% of ArLD patients died in hospital. 13% had no EALoL, 29% just one EALoL but 22% had >5, many for paracentesis. Acute decompensation, septicaemia and bleeds were among the commonest presentations. 25% died in a final admission of <3 days and 33.2% patients admitted to ITU during last admission. Conclusions: ArLD patients die young and are more likely to come from more deprived and marginalised groups with complex psychosocial problems. Many first emergency admissions are serious, often life-threatening. Impact: Palliative care should be involved early as patients may not survive an admission and to support parallel planning for discussions during recurrent admissions.